Therapeutic interleukin-6 blockade reverses transforming growth factor-beta pathway activation in dermal fibroblasts: insights from the faSScinate clinical trial in systemic sclerosis. Issue 9 (31st May 2018) - Denton, Christopher P; Ong, Voon H; Xu, Shiwen; Chen-Harris, Haiyin; Modrusan, Zora; Lafyatis, Robert; Khanna, Dinesh; Jahreis, Angelika; Siegel, Jeffrey; Sornasse, Thierry
Abstract : Objectives: Skin fibrosis mediated by activated dermal fibroblasts is a hallmark of systemic sclerosis (SSc), especially in the subset of patients with diffuse disease. Transforming growth factor-beta (TGFβ) and interleukin-6 (IL-6) are key candidate mediators in SSc. Our aim was to elucidate the specific effect of IL-6 pathway blockade on the biology of SSc fibroblasts in vivo by using samples from a unique clinical experiment—the faSScinate study—in which patients with SSc were treated for 24 weeks with tocilizumab (TCZ), an IL-6 receptor-α inhibitor. Methods: We analysed the molecular, functional and genomic characteristics of explant fibroblasts cultured from matched skin biopsy samples collected at baseline and at week 24 from 12 patients receiving placebo (n=6) or TCZ (n=6) and compared these with matched healthy control fibroblast strains. Results: The hallmark functional and molecular-activated phenotype was defined in SSc samples and was stable over 24 weeks in placebo-treated cases. RNA sequencing analysis robustly defined key dysregulated pathways likely to drive SSc fibroblast activation in vivo. Treatment with TCZ for 24 weeks profoundly altered the biological characteristics of explant dermal fibroblasts by normalising functional properties and reversing gene expression profiles dominated by TGFβ-regulated genes and molecular pathways. Conclusions: We demonstrated the exceptional value of using explant dermal fibroblast cultures from a well-designed trial in SSc to provide a molecular framework linking IL-6 to key profibrotic pathways. The profound impact of IL-6R blockade on the activated fibroblast phenotype highlights the potential of IL-6 as a therapeutic target in SSc and other fibrotic diseases. Trial registration number: NCT01532869 ; Post-results.